2016
DOI: 10.1007/s13296-016-3019-7
|View full text |Cite
|
Sign up to set email alerts
|

Frusta structure designing to improve quasi-static axial crushing performances of triangular tubes

Abstract: To improve quasi-static axial crushing performances of thin-wallled triangular tubes, frusta structures were designed and fabricated. Quasi-static axial compression experiments were carried out to reveal the collapse mode and energy absorption characteristic of the triangular frusta tube. Peak loads and mean crushing forces (MCFs) of tubes with different taper angles were compared. In-extensible and extensible collapse modes were suggested to predict the MCF of the triangular frusta tube with small and great t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similarly, the deformation mode of square tubes could be classified into the extensional mode, inextensional mode, asymmetric mixed mode and non-compact crushing mode [51]. The triangular tubes were also studied in literature [52][53][54], however, the energy absorption capacity of the triangular tubes was the worst of all the tubes owing to the minimum corners [55]. Furthermore, some other novel tubes were proposed to improved mechanical properties.…”
Section: Tubementioning
confidence: 99%
“…Similarly, the deformation mode of square tubes could be classified into the extensional mode, inextensional mode, asymmetric mixed mode and non-compact crushing mode [51]. The triangular tubes were also studied in literature [52][53][54], however, the energy absorption capacity of the triangular tubes was the worst of all the tubes owing to the minimum corners [55]. Furthermore, some other novel tubes were proposed to improved mechanical properties.…”
Section: Tubementioning
confidence: 99%
“…They found that Carbon Fibre Reinforced Polymer (CFRP) tube with winding angle of 25°have the highest SEA. Hong et al 2016 [14] researched that the mean crushing force decreasing when the taper angle is increasing and when taper angles get larger and larger the energy absorption stability factor is close to 1. Yang et al 2016 [15] stated that the crushing force is not only depends on the thickness of the fibre layer but it also dependent on the fibre orientation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the length-to-thickness ratio and the diameter-to-thickness ratio had important influences on the deformation mode of the metallic tube. As for the tube cross-section, attentions were paid to different cross-sectional shapes such as circular, 5 square, 6,7 triangular, 8 hexagonal, 9,10 octagonal, 11 etc. Among them, circular tubes have attracted most attention because of its strong energy absorption capability and ease of manufacturing.…”
Section: Introductionmentioning
confidence: 99%